THE BAR INSTITUTE AND ITS ROLE IN THE ECONOMIC PROCESS - Malika Tollibaeva Tollibaeva (PT. Antis International Publisher, 2026)
Objective: The bar institute constitutes a fundamental component of the legal system, ensuring the effective protection of legal rights and interests of individuals and business entities within economic processes. This article examines the institutional role of the bar in economic proceedings, emphasizing the importance of lawyers’ professional independence, ethical standards, and functional versatility. Method: Using a doctrinal and comparative legal methodology, the study analyzes the participation of lawyers not only as legal representatives but also as legal service providers under civil-law contracts, arbitrators in arbitration and international commercial tribunals, and court administrators in insolvency and economic cases. Results: The findings demonstrate that maintaining the independence of lawyers through civil-law contractual arrangements enhances impartiality, prevents conflicts of interest, and strengthens access to justice. Furthermore, the study highlights that lawyers’ involvement in alternative dispute resolution mechanisms and court administration contributes significantly to procedural efficiency and economic stability. Novelty: The article concludes that the bar institute plays a decisive role in safeguarding the rule of law, promoting fair economic dispute resolution, and supporting sustainable economic development in line with international legal standards.